Emotionally Neutral Stimuli Are Not Neutral in Schizophrenia: A Mini Review of Functional Neuroimaging Studies - Potvin, Stéphane; Tikàsz, Andràs; Mendrek, Adrianna (Frontiers in Psychiatry, 2016)
Reliable evidence shows that schizophrenia patients tend to experience negative emotions when presented with emotionally neutral stimuli. Similarly, several functional neuroimaging studies show that schizophrenia patients have increased activations in response to neutral material. However, results are heterogeneous. Here, we review the functional neuro-imaging studies that have addressed this research question. Based on the 36 functional neuroimaging studies that we retrieved, it seems that the increased brain reactivity to neutral stimuli is fairly common in schizophrenia, but that the regions involved vary considerably, apart from the amygdala. Prefrontal and cingulate sub-regions and the hippocampus may also be involved. By contrasts, results in individuals at risk for psychosis are less consistent. In schizophrenia patients, results are less consistent in the case of studies using non-facial stimuli, explicit processing paradigms and/or event-related designs. This means that human faces may convey subtle information (e.g. trustworthiness) other than basic emotional expressions. It also means that the aberrant brain reactivity to neutral stimuli is less likely to occur when experimental paradigms are too cognitively demanding as well as in studies lacking statistical power. The main hypothesis proposed to account for this increased brain reactivity to neutral stimuli is the aberrant salience hypothesis of psychosis. Other investigators propose that the aberrant brain reactivity to neutral stimuli in schizophrenia results from abnormal associative learning, untrustworthiness judgements, priming effects and/or reduced habituation to neutral stimuli. In the future, the effects of antipsychotics on this aberrant brain reactivity will need to be determined, as well as the potential implication of sex/gender.